Summary Record of Discussions of the National Development Council(NDC) Meetings Five Decades of Nation Building (Fifty NDC Meetings) Vol - III (26th To 35th Meetings) - Planning Commission (Planning Commission, 1969)
The question of a change in the present Financial Year has been considered a number of times in the past. More recently, a Study Team of the Administrative Reforms Commission went in detail into this question and after considering the various alternatives and after discussions with all concerned, including the representatives of State Governments, recommended as follows: The alternatives are several and the criteria to be applied many. The conclusion one may reach is, in the last analysis, a matter of priorities. Should the accent be on the efficacy of performance or the accuracy of revenue budgeting on the convenience of legislators or the accuracy of expenditure estimation. Since no one solution reconciles all these, what particular balance of advantage should be regarded as justifying a disturbance of the status quo with its attendant disadvantages. We have considered these questions and feel that, if the status quo is to be changed, the balance of advantage would lie in favour of 1st October, more especially from the point of view of performance on which we lay emphasis throughout this report.
Government of India Planning Commission
Government of India Planning Commission